Decolonial Pedagogy: Towards the Configuration of Decolonizing Pedagogical Praxes - Ortiz Ocaña, Alexander Luis (2018)
The decolonial turn is more concerned about issue of ideopolitics, epistemics, and epistemology than problems by discipline (pedagogical, curricular and didactic), and its preocupation with the evaluation of learning outcomes is almost non-existent. We have not worked with the breadth and depth of decoloniality in education. It is necessary to decolonize the categorical system of pedagogy, curriculum, and didactics. It is urgent to make a decolonial reading of the genealogy of Educational Sciences. Looking at pedagogy, curriculum, and didactics from a decolonial viewpoint will allow us to uncover the Eurocentric nature of the categorical system of these theories of education and teaching. We must de-link Educational Sciences from Eurocentricity and reveal the doctrinality of education and training, the process that pedagogy hides in its proposal for the notion of training as well as the contradiction between training and emancipation. Doctrinality is the hidden side of the training.